Establishment and Phenotypic Analysis of the Novel Gaucher Disease Mouse Model With the Partially Humanized Gba1 Gene and F213I Mutation - Guo, Jia-ni; Guan, Ming; Jiang, Nan; Li, Na; Li, Ya-jun; Zhang, Jin; Ma, Duan (Frontiers in Genetics, 2022)
Gaucher disease (GD) is an autosomal recessive lysosomal storage disorder caused by mutations in the GBA gene, which produces the GCase protein. There are more than 300 mutations reported in GBA, among which L444P and F213I are the most common in Chinese population，while the function of F213I mutation remains elusive. This study aims to establish the GD mouse model of partially humanized Gba gene with F213I mutation. In vitro GCase activity assays showed that the product of partially humanized Gba gene, in which the mouse exons 5-7 were replace by the corresponding human exons, displayed similar activity with the wild-type mouse Gba, while the F213I mutation in the humanized Gba led to significant decrease in enzyme activity. ES cell targeting was used to establish the mice expressing the partially humanized Gba-F213I. GbaF213I/+ mice did not show obviously abnormal phenotypes, but homozygous GbaF213I/F213I mice died within 24 hours after birth, whose epidermal stratum corneum were abnormal from the wild-type. The activity of GCase in GbaF213I/F213I mice greatly decreased. In conclusion, our results showed that homozygous F213I mutation is lethal for newborn mice and the GD model mice with partially humanized GBA and F213I mutation was developed.